The Australian primary healthcare experiment: a national survey of Medicare Locals - Robinson, Suzanne; Varhol, Richard; Ramamurthy, Vijaya; Denehy, M.; Hendrie, Delia; O'Leary, Peter; Selvey, Linda (B M J Group, 2015)
Objective - The objectives of this study are to evaluate the development and implementation of Medicare Locals as new primary care organisations and consider the implications of these findings for the wider challenge of strengthening primary healthcare in Australia and internationally. Design - National survey of Medicare Locals which involved the use of content analysis and a descriptive survey tool. Setting - 61 Medicare Locals in Australia. Participants - The survey was distributed electronically to all 61 Medicare Local Chief Executive Officers (CEOs) between October and December 2013. Main outcome measures - The research was interested in exploring the following areas; the form and function of Medicare Locals; the confidence and capacity of Medicare Locals to perform against their objectives around population planning and system integration; their ability to engage relevant stakeholder groups; and the barriers and facilitators to reform. Results - A total of 43 (70%) of Medicare Locals completed the survey with representation from six of the eight Australian states and Territories. Results suggest differences in the form and function of the Medicare Local organisations and considerable diversity in the implementation of Medicare Local organisations across Australia. This diversity and lack of guidance from government impacted on the overall success of the reform. Other barriers to reform included difficulties in stakeholder relationships and limited incentives (financial and other) to drive and influence change. Conclusions - Findings from this study produce important insights for primary care reform in Australia; and internationally it adds to the growing body of knowledge around primary care reform.